Dynamic flux balance analysis of biomass and lipid production by Antarctic thraustochytrid Oblongichytrium sp. RT2316‐13 - Shene, Carolina; Paredes, Paris; Flores, Liset; Leyton, Allison; Asenjo de Leuze, Juan; Chisti, Yusuf (Biotechnology and Bioengineering, 2020)
Production of biomass and lipids in batch cultures of the Antarctic thraustochytridOblongichytriumsp. RT2316-13, is reported. The microorganism proved capable of producing nearly 67% docosahexaenoic acid (DHA) and 15% eicosapentaenoic acid (EPA) in its total lipid fraction. Biomass with a maximum total lipid content of 33.5% (wt/wt) could be produced at 15 degrees C in batch culture using a medium containing glucose (20 g/L), yeast extract (10.5 g/L), and other minor components. A lower culture temperature (5 degrees C) reduced biomass and lipid productivities compared to culture at 15 degrees C, but enhanced the DHA and EPA content of the lipids by 6.4- and 3.3-fold, respectively. Both a simple minimally structured mathematical model and a more complex genome-scale metabolic model (GEM) allowed the fermentation profiles in batch cultures to be satisfactorily simulated, but the GEM provided much greater insight in the biochemical and physiological phenomena underlying the observed behavior. Unlike the simpler model, the GEM could be interrogated for the possible effects of various external factors such as oxygen supply, on the expected outcomes. In silico predictions of oxygen effects were consistent with literature observations for DHA producing thraustochytrids. Instituto Antartico Chileno (INACH) project Inach, Chile RT 23-16 Comision Nacional de Investigacion Cientifica y Tecnologica (CONICYT) CONICYT FONDECYT 3170610 Direccion de Investigacion, Universidad de La Frontera (GAP) Comision Nacional de Investigacion Cientifica y Tecnologica (CONICYT) FB-0001